THERMODYNAMIC PROPERTIES OF NACL SOLUTIONS AT TEMPERATURES LOWER THAN 0°C - Akinfiev N.N.; Mironenko M.V.; Dunaeva A.N.; Grant S.A. (My University, 2000)
The limiting values of NaCl(aq) heat capacity, c0p, 2, at temperatures from 0 to - 25°C and volume, V02 , from 0 to - 15°C, were obtained by the mathematical processing of experimental determinations of heat capacity and density of sodium chloride solutions at temperatures lower than 0°C. Proceeding from these results, the parameters of the Helgeson-Kirkham-Flowers (HKF) equation of state were refined for the species Na+. The Gibbs free energies Of Na+ and Cl- calculated by the HKF equation together with the modified approximations of Pitzer's parameters for calculation of activity coefficients allowed numerical reproduction of the experimental NaCl-H2O phase diagram. This proves the validity of the HKF model for the extrapolation of the limiting thermodynamic properties of aqueous species into low temperatures. The thermodynamic parameters of Na+ and C1- derived in this work enable precise thermodynamic calculations in the system NaCl-H2O at temperatures from 100 to -30°C and a wide range of electrolyte concentration.